Electrochemical Properties of NdCl3 and CeCl3 in Molten LiCl-KCl Eutectic Salt - Seunghyun Kim; Sang-hwan Lee (Applied Sciences, 2020)
NdCl3 and CeCl3 are characterized by the very close proximity of their standard reduction potentials. Thus, they represent the most challenging salt mixtures with respect to decoupling electrochemical responses and calculating concentrations. The goals of this study include the determination of the apparent standard potentials of both Nd3+/Nd2+ and Ce3+/Ce in LiCl-KCl-CeCl3 or NdCl3 mixtures. Matrix and concentration effects on fundamental electrochemical properties are of particular interest, as these thermodynamic properties will impact the ability to use voltammetry to measure concentrations in unknown samples. Several LiCl-KCl-CeCl3 or NdCl3 mixtures with NdCl3/CeCl3 concentrations ranging from 4 to 10 wt% at 753 to 793 K have been explored. For apparent standard potential values of CeCl3, a good agreement was obtained with the literature data, except above 773 K.